Finding Justice in Cyberspace: The Wickedness of Online Gender-Based Violence (GBV) - Nusaibah Edi Nugraha; Sekarayu Tunggadewi Anugraputri (Jurnal Wanita dan Keluarga, 2022)
Gender-Based Violence in Indonesia is generally divided into two categories; kekerasan berdasarkan ranah personal (GBV that takes place in a private setting) and kekerasan berdasarkan komunitas dan negara (GBV that takes place in a public setting). Aside from this, the COVID-19 pandemic has brought to light an equally concerning form of GBV, online GBV. While both have their complexities, there seems to be a jarring gap in how current policy handles offline and online. The objectives of this research are two-fold: (1) to examine online GBV within the context of Indonesia; (2) to explore the nexus between theory and practice regarding online GBV. We found that although both types of GBV are shrouded in hegemonic masculinity, the added layer of the online space makes online GBV more complex, making it a Wicked Problem. The concept of a Wicked Problem is often used to descibe issues with high complexity making it difficult to solve Though at the time of write UU TPKS had not been legalized, the 10 year strugle behind it shows the wickedness behind this issue. As UU TPKS has yet to be implemented, we suggest upscaling grassroot feminist or pro-gender organizations in effort to spread awareness and further combat online GBV.